Die Bahnhofsmission als kirchlicher Ort im Bahnhof - Eurich, Johannes (Evangelische Theologie, 2021)
Railway stations are special places and important elements in urban life. They exist in a dual function of place and node, which is reflected in their service structure. In the station, the station mission provides support and assistance for people in certain life situations. This raises the question of the connection of the station mission as a social service to the church. The place of the "in-between" could hold a development potential for the interaction of parishes and new church places. The railway station mission could, thus, move from a marginal position in the church to a node in the network of church services. At the same time, as an explorative field for inclusion, it could contribute important experiences to inclusion processes.
Gesehen am 04.11.2021
Keywords: Inklusion; Pastoralsoziologie; Bahnhofsmission